SEXUAL CONSENT IN THE ELIMINATION OF SEXUAL VIOLENCE PERSPECTIVES OF FEMINIST LEGAL THEORY AND ISLAMIC LAW: A COMPARATIVE STUDY. - Ratih, Nala; Sutisna, Sutisna; Hambari, Hambari (MIZAN: JOURNAL OF ISLAMIC LAW, 2023)
The critical legal movement in Indonesia is called feminist legal theory (FLT). FLT criticizes laws that have masculine values, they limit social values because the dominant law against men oppresses women. This FLT movement produces the paradigm of sexual consent which is accepted in the laws and regulations in Indonesia. The study describes how sexual consent in the elimination of sexual violence perspective Feminist Legal Theory and Islamic law. The methodology of this study is normative legal research and literature with the approach of legislation (statute approach) and comparison (comparative approach). From this study it can be concluded that sexual consent in the elimination of sexual violence Flt perspective is a sexual activity that is carried out based on consent outside of the consent of one of the parties, including rape. While sexual consent in Islamic law is a relationship that can only be done in a marriage bond outside the marriage bond, the Act includes adultery even though it is done with consent or voluntarily. Sexual consent is not in accordance with the norms of Indonesian life and contrary to Pancasila. Sexual consent as a solution to eliminate sexual violence does not seem to be the answer to the elimination of sexual violence because sexual consent only focuses on “solving the consequences” not “preventing causes”.